PHYTOCHEMICAL SCREENING AND EVALUATION OF IN-VITRO ANTIMICROBIAL ACTIVITY OF DROSERA SPATULATA VAR BAKOENSIS- AN INDIGENOUS CARNIVOROUS PLANT AGAINST RESPIRATORY TRACT INFECTIOUS MICROBES. - G, DILEEP KUMAR; C D S L N, TULASI; G, RAMAKRISHNAIAH (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: In the present study, the phytochemical constituents of Drosera spatulata, have been evaluated and antimicrobial activity was screened against respiratory tract infectious microbes. Methods: The phytochemicals present in Drosera spatulata by qualitative phytochemical assays and the antimicrobial activity along with MIC, MBC and BIC were determined against S. aureus, Klebsiella pneumonia and S.Pneumonia the causative organisms of pulmonary infections, mainly effects the nasal pharynx, trachea, and lungs as well as Aspergillus niger. Results: Aqueous, ethanol, methanol extracts of thick roots, open flower and hair of Drosera spatulata var bakoensis against this pathogenic bacteria and fungi showed high zone of inhibition which estimated by disc-diffusion method as well as minimum inhibition concentration manifestation by the broth microdilution assay followed MBC and BIC. The values of MIC, MBC and BIC obtained were between 0.3-0.9, 0.36-2.25, 0.12 - 0.37 mg/mL. The results revealed that the plant extracts of Drosera spatulata var bakoensis have high potential even at low concentrations values against bacteria and fungi cultures and this results validated by the presence of high amounts of alkaloids, quinones, anthraquinones, flavonoids in the plant extracts. Â Conclusion: In the present study, the results showed the presence of high amounts of alkaloids, flavonoids, quninoes, anthraquinones, terpinoids in Drasera spatulata plant. Â In the antibacterial and antifungal activity, the ethanol and methanol extracts significantly showed the activity against the tested respiratory disease causing bacteria and antifungal properties with zone of inhibition showed more than aqueous extracts at very low concentrations